Program Keluarga Harapan (PKH) Mentoring Strategy on Improving Community Welfare - Ashri Ramadhan; Zainal Fadri; Dani Yoselisa; Iswadi Iswadi; Siska Elasta Putri (Universitas Islam Negeri Mahmud Yunus Batusangkar, 2024)
This research aims to provide a substantial contribution in strengthening understanding of the importance of effective mentoring strategies in the Family Hope Program (PKH) in Nagari Rambat. The main aim of this research is to present concrete evidence regarding the positive influence of PKH assistants on changes and improvements in community welfare. By exploring the experiences of PKH facilitators and involving the active participation of PKH recipient families, this research designs a participatory and community empowerment approach that focuses on implementing the PKH program in Nagari Rangkat, Tanah Datar Regency. Holistic research methods are used to explore comprehensive data and perspectives. Through in-depth interviews, observations and data analysis, this research aims to identify key factors that influence the success of mentoring in achieving PKH program goals, as well as its impact on the level of welfare of local communities.It is hoped that the results of this research will be able to provide a strong empirical basis for formulating policy recommendations and improving the implementation of the PKH program in Nagari Rambat. In addition, it is hoped that the findings from this research can be applied more widely at the national level to enrich and increase the effectiveness of similar programs.